Experimental Evaluation of the Pathogenicity of Different Strains of Schistosoma mansoni - Antônio Aurélio Euzébio; Nádia Regina Borim Zuim; Arício Xavier Linhares; Luiz Augusto Magalhães; Eliana Maria Zanotti-Magalhães (Interdisciplinary Perspectives on Infectious Diseases)
The pathogenesis of three different Schistosoma mansoni strains from the Brazilian states of Minas Gerais (BH strain) and São Paulo (SJ and SD strains) was evaluated in experimentally infected mice. Observations of the most severe clinical cases among local patients treated (SD strain) in the city of Campinas (São Paulo, Brazil) formed the basis of this study. Mice were used as definitive hosts and were infected with cercariae from Biomphalaria tenagophila (SJ and SD strains) and Biomphalaria glabrata (BH strains). The parameters analyzed were as follows: number of S. mansoni eggs in mice feces; number of granulomas per tissue area in liver, spleen, lungs, pancreas, and ascending colon; measurements of hepatic and intestinal granulomas; number of adult worms; and measurements of trematode eggs. The comparison among the three strains indicated that the SD strain, isolated in Campinas, presented a higher worm recovery relative to the number of penetrating cercariae. In addition, when compared to the SJ and BH strains, the SD strain demonstrated similar pathogenicity to the BH strain, with a greater quantity of granulomas in the viscera, as well as larger granulomas and eggs. Furthermore, a greater quantity of trematode eggs was also shed in the feces.